Patterns in fish naming ability in two fishing communities of Myanmar - Aung Si; Aung Kyawphyo (BMC, 2023)
Abstract Background To date, there is little reliable information on the fish names used by two fishing communities of Myanmar, namely Intha (Inle Lake) and Rakhine (Bay of Bengal). Moreover, there have been no systematic studies on the distribution of fish-related traditional knowledge in these two communities. As there can be high levels of intra-community variation in traditional ecological knowledge, it is important to investigate this variation along the lines of key social variables. Methods Fieldwork was carried out in both communities and involved the presentation of visual stimuli (colour pictures of locally relevant fish species) to respondents, and asking for a name in the local language. The stimuli consisted of 43 and 218 fish species for Intha and Rakhine, respectively. The responses were analysed in terms of respondent age and occupation for both communities, plus village location for Intha and gender whenever both genders were represented in a sufficiently large number in the sample. Results Fish name lists were generated for both languages, taking into account lexical variation, as well as the number of people able to name each fish. The two communities differed markedly in the way fish knowledge was distributed. Overall, younger Intha knew fewer fish names, but there was little to no difference in fish knowledge among the Intha on the basis of occupation, location or gender. In contrast, the differences were very marked among Rakhine respondents. Conclusions The reduced fish knowledge of younger Intha may be ascribed to environmental disturbances that have caused many fish to go locally extinct. The otherwise homogenous distribution of fish knowledge in the Intha community may be due to the small number of species that people are required to learn. This idea needs to be tested with a larger sample of respondents. Among the Rakhine, a number of factors are responsible for the observed variation; these include a steep learning curve among younger fishermen, the difference in fish species encountered by fishermen and sellers, highly variable dietary preferences among the general populace and differing gender roles in the context of market visits. The authors are in full agreement with previous research that advocates a variationist approach to the study of traditional ecological knowledge.